DETECTION OF FIMA GENE FROM VIRIDANS GROUP STREPTOCOCCI (VGS) ISOLATED FROM ORAL CAVITY OF HEALTHY POPULATION - R. SANDHIYA; S. SENTHIL KUMAR; THANGAM MENON (International Journal of Pharma and Bio Sciences, 2014)
Viridans group streptococci (VGS) are commensals of human oral cavity. They are the major cause of native valve endocarditis in immunocompetent individuals. Among the factors contributing to its virulence, its ability to adhere to host cells is considered to be important. FimA is an important virulence factor which promotes the adherence of bacteria to fibrin in vegetations of infective endocarditis (IE) patients. FimA is an adhesin protein encoded by fimA gene. The aim of the present study was to detect fimA gene among viridans group streptococci by Polymerase Chain Reaction (PCR). Viridans group streptococci including S. mitis (11), S. salivarius(11), S. oralis(1), S. sanguinis(2)and S. parasanguinus(1) isolated from oral cavity of healthy population were included in the study. The fimA gene was detected by PCR. Of the strains, only one (3.8%) was positive for fimA gene and it belonged to species S. parasanguinus. None of the other species were positive for fimA gene. Although fimA gene is considered as a major virulence factor and associated with IE, our data suggests that it may also be present in S. parasanguinus strains isolated from oral cavity of healthy population.